Auxiliary equation is "D^4 +2D^3-3D^2 = 0" (1)
Solving it, we get "D^2(D-1)(D+3) = 0"
"D = 0,0,1,-3"
Then "y = c_1+c_2x+c_3e^{x}+c_4e^{-3x}"
For particular integral,
For "x^2",
Let "y = ax^4 + bx^3+cx^2 +dx+e" be it's solution
then
"y'' = 12ax^2 +6bx +2c"
"y''' = 24ax + 6b"
"y'''' = 24a"
Putting values in equation "D^4+2D^3-3D^2 = x^2" , we get
"-36ax^2 + (48a-6b)x + (24a+12b-6c) = x^2"
comparing powers,
we get "a = -\\frac{1}{36}, b = -\\frac{2}{27}, c = -\\frac{7}{27}"
then P.I. for "x^2" is, "-\\frac{1}{36}x^4 - \\frac{2}{27}x^3 - \\frac{7}{27}x^2"
P.I. for "3e^{2x}" ,
"\\frac{1}{D^4+2D^3-3D^2}e^{2x} = e^{2x}\\frac{1}{2^4+(2\\times 2^3)-(3\\times 2^2)} = \\frac{3}{20}e^{2x}"
P.I. for 4sin(x)
"\\frac{1}{D^4+2D^3-3D^2}4sin(x) = \\frac{1}{D^2(D^2+2D-3)}4sin(x)"
"= \\frac{1}{(-1^2)(-1^2+2D-3)}4sin(x) = \\frac{1}{2-D}2sin(x) = -2\\frac{(D+2)}{D^2 - 4}sin(x)"
"= -2\\frac{cos(x)+2sin(x)}{-1-4} = \\frac{2}{5}(cos(x)+2sin(x))"
Solution of the differential equation is
"y = c_1+c_2x+c_3e^{x}+c_4e^{-3x}-\\frac{1}{36}x^4 - \\frac{2}{27}x^3 - \\frac{7}{27}x^2+\\frac{3}{20}e^{2x} +\\frac{2}{5}(cos(x)+2sin(x))"
Comments
Leave a comment